Analisis sisa makanan dan biaya sisa makanan pasien skizofrenia rawat inap di Rumah Sakit Jiwa Madani Palu - Irawati Irawati; Yeni Prawiningdyah; R Dwi Budiningsari (Jurnal Gizi Klinik Indonesia, 2010)
Background: Food has not only considerable therapeutic but also economic value. The success of food provision is related to leftover that can indicate less optimum food provision in hospitals. Leftover indicates the presence of wasted cost.Objective: To analyze leftover and cost of leftover of schizophrenic inpatients at Madani Mental Hospital Palu.Method: The study used cross sectional method. Subject of the study were schizophrenic inpatients who got ordinary food portion had been mobilized from acute to common room 2 x 24 hours, put in class 3 room, were able to eat food on their own with exclusion criteria the presence of accompanying diseases that could affect appetite and got food from outside the hospital (n = 35). Data were analyzed quantitatively using chi square to find out factors related with the presence of leftover. Data of respondent characteristics and cost of leftover were analyzed descriptively.Result: There was difference in leftover based on sex and portion in particular rice and animal side dish leftover (p <0.05) but there was no significant difference in age, type of schizophrenic disease, duration of hospitalization and previous hospitalization (p ≥ 0.05). Total cost of wasted food a day was Rp 1,529.33.Conclusion: There was difference in leftover based on sex and portion particularly rice and animal side dish leftover. Average amount of leftover varied according to eating time and types of food. Cost of wasted food varied according to types of food.